PENGARUH SISTEM INFORMASI AKUNTANSI, KOMPETENSI SUMBER DAYA MANUSIA,DAN KOMITMEN ORGANISASI TERHADAP KUALITAS LAPORAN KEUANGAN BADAN KEUANGAN DAERAH SUKOHARJO - Rahayu, Rezky; Eko Triyanto (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The implementation of this research aims to "analyze the quality of financial reports of the Sukoharjo Regional Finance Agency which is influenced by organizational commitment, human resource competence, competence, and accounting information systems". Then the subject of the research is Civil Servants at the Sukoharjo Regional Finance Agency with a total population of 72 people. Furthermore, the testing method implements multiple linear regression analysis and utilizes SPSS software in processing research data. Based on the testing and analysis carried out, it is obtained that "the quality of the financial statements of the Sukoharjo Regional Finance Agency is significantly influenced by organizational commitment, human resource competence, competence, and accounting information systems partially and simultaneously".